Recent Research Trends and Advancements in Computational Linguistics - Ganesan, R.; Thangamani, M.; Ibrahim, S. Jafar Ali (International Journal of Psychosocial Rehabilitation, 2020)
AI and machine learning change everything about computing. Innovations in the processing of natural languages change everything about interaction between human computers. Some of these developments have become possible due to ground—breaking natural language processing work. The scientific study of language from a machine viewpoint is ascribed as computational linguistics (CL). CL's computer work focuses on natural language modelling and is based on computing and artificial intelligence. The goal of machine linguistics is to build software to interpret the natural language that we use to interact in everyday life. Scientists in the field of Informatics have been faced with interactions between people and equipment. The rapid and exponential growth of regimented knowledge such as records, databases and social media has rendered it even more important to predict the future of digital linguistics. In fact, the capacity of the providers to use whatever information available for tactical insight and decision making can be improved significantly by human and machine connectivity. We also addressed global trends and advances in machine linguistics in this research article.